An investigation into the thermal management and control of ceramic injection moulding die-tools - Bianchi, Maria Floriana (2020)
Ceramic Injection Moulding (CIM) is an extensively used process in the mass production of complex components, consisting of three stages: injection moulding, debinding (i.e. binder removal) and sintering. In the aerospace industry, CIM is employed to make ceramic cores, which are sacrificial components used to shape the internal cooling channels of high-pressure turbine blades and vanes, manufactured by investment casting. The injection moulding of cores presents significant challenges due to their geometry, characterised by adjoined features having uneven wall thickness: this determines differential cooling rates along the part arising throughout the moulding process, which, in turn, cause several flaws in finished cores (e.g. warpage, cracking and poor surface quality). Even higher mouldability challenges are brought by the increasing requirements of turbine working temperatures, calling for higher complexity of core geometries. To cope with this, suitable due-tool thermal control approaches have to be employed. However, state-of-the-art temperature control methods present strong limitations, as they aim at achieving a uniform cavity temperature, which do not prevent the development of uneven cooling rates in parts with differential wall thickness.